2003
DOI: 10.2746/042516403776148219
|View full text |Cite
|
Sign up to set email alerts
|

The sacroiliac joints: evaluation using nuclear scintigraphy. Part 1: The normal horse

Abstract: Summary Reasons for performing study: Sacroiliac (SI) disease is recognised as a cause of poorhindlimb action but differential diagnosis is often difficult. Hypotheses: That in clinically normal horses there would be a significant difference in the ratio of radiopharmaceutical uptake (RU) between the fifth lumbar vertebra (L5) and each tuber sacrale (TS) and between L5 and each SI joint; and that these ratios would alter with age, but ratios would be bilaterally symmetrical. Methods: Dorsal scintigraphic im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…Similar patterns of radiopharmaceutical uptake have been documented in horses with sacroiliac joint region pain and normal horses . Diagnostic analgesia can confirm the presence of pain in the sacroiliac joint region .…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Similar patterns of radiopharmaceutical uptake have been documented in horses with sacroiliac joint region pain and normal horses . Diagnostic analgesia can confirm the presence of pain in the sacroiliac joint region .…”
Section: Discussionsupporting
confidence: 63%
“…Unlike hindlimb proximal suspensory desmopathy, there was no association between lesion severity as determined by ultrasonography and the presence of increased radiopharmaceutical uptake, however severely lame horses with mild ultrasonographic abnormalities may have increased radiopharmaceutical uptake reflecting injury at the enthesis. Although stress fractures are infrequently seen in sports horses compared with racehorses, one exception is proximal palmar cortical stress fracture (incomplete longitudinal fracture) of the third metacarpal bone which occurs in mature sports horses . There is invariably increased radiopharmaceutical uptake, which must be distinguished from an avulsion fracture or proximal suspensory desmitis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies (Tucker et al 1998;Dyson et al 2001Dyson et al , 2003a have investigated the scintigraphic appearance of the sacroiliac joint in normal and diseased horses. It was concluded that the scintigraphic appearance of the sacroiliac joint is influenced by age and that there is a wide range in scintigraphic uptake between horses.…”
Section: Anatomymentioning
confidence: 99%
“…Reference has been made to the use of local analgesia (Dyson et al 2001;Haussler 2003), but there are no published studies documenting the results. The use of nuclear scintigraphy as an aid to diagnosis has been recently described (Tucker et al 1998;Philipp and Ueltschi 1999;Dyson et al 2001Dyson et al , 2003a.…”
Section: Introductionmentioning
confidence: 99%